Economic Transformation of Indonesian Migrant Workers Into Sustainable Independent Entrepreneurs - Sunaryono, Sunaryono; Hardayu, Audisty Prana; Febrianti, Sukma; Trisnawati, Ema; Yulianto, Yulianto (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Indonesian migrant workers contribute significantly to household and national economies through remittances; however, many face challenges in achieving sustainable economic independence after migration. This community service activity aims to promote the economic transformation of Indonesian migrant workers into sustainable independent entrepreneurs through a participatory and dialogical approach. The program was conducted in Kuching, Malaysia, involving Indonesian migrant workers through direct visits and interactive discussions facilitated by the community service team in collaboration with the Indonesian Embassy. The implementation method included knowledge-sharing sessions, reflective dialogue, and experiential discussions focused on entrepreneurship awareness and post-migration economic planning. The results indicate an increased understanding among participants regarding sustainable entrepreneurship, a shift in mindset from short-term income dependency toward long-term economic planning, and enhanced motivation to utilize work experience and skills as entrepreneurial capital. This activity contributes to strengthening the economic readiness of Indonesian migrant workers and offers a replicable community-based empowerment model for similar initiatives in other migrant destination areas.